Sodium Selenite Improves In Vitro Maturation of Bos primigenius taurus Oocytes - Lizarraga, Raúl Martín (2019)
Selenium (Se) is an essential trace element with important functions in animals and whose deficiency is associated with reproductive failures. The aim of this study was to investigate the effect of Se concentrations during in vitro maturation (IVM) of Bos taurus oocyte within the reference ranges for Se status in cattle. For this purpose, Aberdeen Angus cumulus–oocyte complexes (COCs) were matured in IVM medium supplemented with 0, 10, 50, and 100 ng/mL Se (control, deficient, marginal, and adequate, respectively). The results demonstrated that marginal and adequate Se concentrations added during IVM increased viability and non-apoptotic cumulus cells (CC). Moreover, the addition of Se to culture media decreased malondialdehyde level in COC with all studied concentrations and increased total glutathione content in CC and oocytes with 10 ng/mL Se. On the other hand, total antioxidant capacity of COC, nuclear maturation, and the developmental capacity of oocytes were not modified by Se supplementation. However, 10 ng/mL Se increased hatching rate. In conclusion, supplementation with 10 ng/mL Se during in vitro maturation of Bos primigenius taurus oocytes should be considered to improve embryo quality.